I-DOSING - DIGITAL DRUG? - Boskovic, Milica; Putnik, Nenad (Political Review, 2024)
In 1839, Heinrich Wilhelm Dove discovered that two constant tones, emitted at slightly different frequencies at each ear, conjured the listener to register this as a fast rhythm, and this phenomenon was called binaural beats. Among the authors today, there are conflicting opinions about whether this phenomenon can be "abused". Binaural beats are brainwave entertainment technology, designed to put the brain into the same activity level as when meditating using traditional methods. Binaural beats affect mood, concentration and sleep by modifying brain waves based on the brain’s response patterns to dichotomous and different frequencies. Therapy by music, as well as the use of certain specially arranged sounds to relieve anxiety, stress or health problems such as high blood pressure, are not unknown and are even widely accepted and used in different branches of medicine. However, when scientists, and companies in particular, point out that binaural beats, used in a certain way, can affect the state of consciousness and behaviour, referring to the feelings created by drug use, then it raises serious questions. Digital drugs or binaural beats that support the creation of a feeling similar to that of drug abuse, is a phenomenon about which less is known, Considering that, especially the young population, is already being treated today. Medical treatments have been created to get rid of addiction to the Internet, smartphones and similar technologies, it is clear that any innovation, like medicine, can also have the possibility of abuse. Bearing this in mind, binaural tones created and used to intentionally influence the mood and flow of thoughts (not part of medical treatment under professional supervision) can and must be viewed as a security threat in socio-pathological phenomena.